Outcomes of Distal Third Tibial Shaft Fractures Treated by Modified Interlocking Intramedullary Tibial Nail - Rahman, Md Ziaur; Siddique, Md Zillur Rahman; Shah, Md Asaduzzaman; Hossain, Md Younus; Islam, Md Robiul; Mondol, Abu Said Md Rahenur; Anwar, Md Mahfuj Ul (Journal of Rangpur Medical College, 2025)
Introduction: Distal third tibial shaft fractures are challenging to manage due to poor soft tissue coverage and high risk of malalignment and delayed healing. Modified interlocking intramedullary nailing offers improved stability and early mobilization compared to conventional methods. Objective: This study aimed to evaluate the clinical, radiological, functional, and structural outcomes of distal third tibial shaft fractures treated with the modified interlocking intramedullary tibial nail. Methods: This prospective observational study was conducted in the Department of Orthopaedic Surgery at the National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka, Bangladesh from July 2016 to June 2018. A total of 30 patients aged between 18 and 65 years of both sexes, presenting with distal third tibial shaft fractures (AO classification types 42A1–3 and 42B1–3) were included. Data was analyzed using the Statistical Package for Social Sciences (SPSS), version 22. Results: In this study of 30 patients with distal third tibial shaft fractures treated using a modified interlocking intramedullary tibial nail, the majority achieved radiological union within 16–18 weeks and full weight bearing by 14–16 weeks. Most patients experienced no pain, deformity, or significant motion loss, with 90% showing excellent-to-good functional recovery per the Karlström–Olerud score. Overall, the procedure provided stable fixation, rapid healing, and satisfactory functional and structural outcomes with minimal complications. Conclusion: Treatment of distal third tibial shaft fractures with the modified interlocking intramedullary tibial nail yields excellent clinical, radiological, functional, and structural outcomes with minimal complications. J Rang Med Col. 2025 Sep;10(2): 156-162